1930
DOI: 10.1007/bf01330300
|View full text |Cite
|
Sign up to set email alerts
|

R�ntgenographische Intensit�tsmessungen an gest�rten Gittern

Abstract: Die Brauchbarkeit der rSntgenographisehen Intensit~tsmessung fiir das Studium yon kleinen Struktur~inderungen dutch mechanische, chemische, thermische und elektrische Einfliisse wird besprochen. Mit Hi[fe des Ionisationsspektrometers werden die Intensit~ten der Wiirfelflfiche von K C1 w~hrend des Deformatiensvorganges in Abh~ngigkeit yon der plastischen Deformation gemessen. Das bei (200) and (400) beobaehtete Ansteigen der Intensit~t wird durch die infolge der Deformation grSi}er werdenden Verwerfungen der Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1934
1934
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Several papers have attempted to connect the observed line intensities and widths with the internal distortions. [1][2][3][4][5][6] Little attention has been given to the continuous background scattering arising from the distortions. The experimental conditions for this type of research are not easy, because other effects such as fluorescent radiation, Compton radiation, diffuse scattering by air, coherent temperature scattering and background owing to the continuous x-ray spectrum, all contribute to the observed background.…”
Section: (B) Energy Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have attempted to connect the observed line intensities and widths with the internal distortions. [1][2][3][4][5][6] Little attention has been given to the continuous background scattering arising from the distortions. The experimental conditions for this type of research are not easy, because other effects such as fluorescent radiation, Compton radiation, diffuse scattering by air, coherent temperature scattering and background owing to the continuous x-ray spectrum, all contribute to the observed background.…”
Section: (B) Energy Spectrummentioning
confidence: 99%
“…We present here an outline of this work: some details that will be omitted may be found elsewhere. 1 The first attempts to detect the deflection of cosmic particles by the magnetic field in an iron core were made in 1930 by Rossi 2 and Mott-Smith 3 independently. Their apparatus were Mott-Smith obtained a negative result.…”
Section: Introductionmentioning
confidence: 99%
“…Already ten ycars ago this method was applied (12,13,34,35,39,41,58,82,95) and the following results were obtained: Sative and regenerated cellulose is built up of micellae which have an average Recently an independent possibility of determining the average width of crystallized portions was worked out (22, 52, 54, 68) on the following basis: The larger the spacings (d) of a lattice, the smaller mill be the angle (29) under which a certain x-ray waw length is reflected. Already ten ycars ago this method was applied (12,13,34,35,39,41,58,82,95) and the following results were obtained: Sative and regenerated cellulose is built up of micellae which have an average Recently an independent possibility of determining the average width of crystallized portions was worked out (22, 52, 54, 68) on the following basis: The larger the spacings (d) of a lattice, the smaller mill be the angle (29) under which a certain x-ray waw length is reflected.…”
Section: B Thr Introduction Of Mznute Crystals In the Intermicellar mentioning
confidence: 99%
“…X-ray line broadening indicated that the crystals were either very imperfect or very small (42). Assuming the latter, in 1928 Hengstenberg and Mark (43) estimated that the crystallites of ramie, a form of native cellulose, were about 55 Å wide and over 600 Å long by this method. It had already been established that the polymer chain passed through many unit cells.…”
Section: The Fringed Micelle Modelmentioning
confidence: 97%
“…For example, the structure of the amino acid phenylalanine in a protein may be written Spider webs Coir Ramie Jute Figure 6. 43 The cell walls of a tracheid or wood fiber have several layers, each with a different orientation of microfibrils (164). ML, middle lamella, composed of lignin; P, primary wall; S 1 , S 2 , S 3 , layers of the secondary wall; W, warty layer.…”
Section: Natural Fibersmentioning
confidence: 99%